CONTENT MARKETING OF SPORTS ACTIVITIES AS A TOURIST INFLUENCE IN THE SUCRE DESTINATION - Zambrano, Lilia Moncerrate Villacis; Calderón, Jonathan Eudaldo Quezada (Seven Editora, 2025)
The main objective of the research was to evaluate how content marketing of sports activities influences the tourist attraction to the destination Sucre, In the research a quantitative and qualitative approach was used, a descriptive and exploratory design was used, the technique was the survey, a non-probabilistic convenience sampling was chosen, to measure reliability and tabulate the data the spss 26 program was used, giving a reliability of 0.979, it was concluded that content marketing applied to sports activities in Sucre are key strategies to enhance tourist attractions that impact the positioning of the tourist destination as a reference in experiences that visualize a significant dynamic that supports sport in a playful expression of integration of creative and authentic content linked to sporting events. To achieve this, it is essential to attract visitors interested in unique experiences, fostering cultural interaction and sustainable tourism development. By linking sports promotion with the destination's identity, Sucre is projected as an attractive and competitive place in the regional tourism market. This combination of content marketing, sports, and culture drives local economic development, encourages community participation, and reinforces a sense of identity, consolidating Sucre as a vibrant and constantly growing destination.DOI: https://doi.org/10.56238/sevened2025.026-028